Scientific and Natural Law Analyses of Homosexuality: A Methodological Study - Pope, Stephen J. (Journal of religious ethics, 1997)
Natural law ethicists have typically argued that homosexual activity is immoral because it is "unnatural." Recent scientific information and theories, on the other hand, have been used to challenge this description and to provide moral backing for sexual activity among homosexuals. This paper traces some of the recent scientific claims about possible natural bases of homosexuality and then examines what significance these claims might have for several contemporary forms of natural law ethics. It argues that natural law assessments ought to develop a careful and informed account of whether or to what extent homosexual activity can contribute to integral human flourishing rather than focusing on its status as "natural" or "unnatural" per se.